Korelasi antara Implementasi E-Government dan Tingkat Partisipasi Masyarakat dalam Pengawasan Publik di Daerah - Haidar Adam (Universitas Pangeran Diponegoro Nganjuk, 2026)
The implementation of e-government in local governments in Indonesia is not only aimed at improving bureaucratic efficiency and public service quality but also at encouraging community participation in public oversight. However, the correlation between the maturity level of e-government implementation and the level of community participation in oversight functions has not been extensively studied empirically. This article aims to analyze the correlation between the implementation of e-government and the level of community participation in public oversight at the local level. Using a normative-empirical legal research method with a statutory and socio-legal approach, this study finds that the correlation is not automatically linear. The success of e-government in encouraging oversight participation is highly dependent on several intervening variables, including digital literacy levels, the quality of public information disclosure, the responsiveness of local governments to feedback, and inclusive technology accessibility. The study concludes that to strengthen this correlation, local governments need to develop e-government not only as an administrative tool but also as a genuine participatory platform that is accessible, responsive, and supported by strong regulations regarding public information disclosure.